Penguatan UMKM Desa Pesisir melalui Legalitas Usaha, Teknologi Digital, dan Inovasi Briket Limbah Jagung - Dina, Karina Farkha; Mardisiwi, Ririh Sekar; Fithor, Alin (Maslahah: Jurnal Pengabdian Masyarakat, 2025)
Community service aims to increase the competitiveness of MSMEs in Lebakwangi Village, Jatinegara District, requiring three main strategies: business legality, digital transformation, and agricultural waste-based product innovation. Digital marketing training with Google Maps, social media, simple financial applications, and innovation in making environmentally friendly briquettes from corn waste. The results of the activity show that the majority of MSMEs have succeeded in obtaining business legality, mastering digital marketing strategies, and producing briquettes, which have the potential to become superior village commodities. The impacts achieved include increasing legal awareness, strengthening digital capacity, reducing agricultural waste, and creating new business opportunities. Thus, legality, digitalization, and product innovation have proven to be effective in sustainably empowering MSMEs.